The impact of a single episode of remote ischemic preconditioning on myocardial injury after elective percutaneous coronary intervention - Yılmaztepe, Mustafa A.; Taylan, Gökay; Aktoz, Meryem; Gürlertop, Hanefi Y.; Aksoy, Yüksel; Özçelik, Fatih; Yalta, Kenan; Ekuklu, Galip (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Myocardial injury after percutaneous coronary intervention (PCI) occurs in approximately 30% of procedures, and is related to worse prognosis. Effects of remote ischemic preconditioning (RIPC) on reperfusion injury have been investigated before, yielding conflicting results. Aim : To assess the impact of a single episode of RIPC on myocardial injury after elective PCI. Material and methods : One hundred and four patients undergoing elective PCI, with normal baseline cardiac troponin-I (cTn-I) values, were randomized to two groups. Two patients were excluded due to data loss, and 102 patients were analyzed. Five minutes of ischemic preconditioning was delivered just before the intervention to the preconditioning group, by inflating the blood pressure cuff up to 200 mm Hg on the non-dominant arm. Postprocedural 16th hour cTn-I, cTn-I (difference between the 16th h and baseline cTn-I values) and the prevalence of type 4a myocardial infarction were compared between the two groups. Results : Median cTn-I values after the procedure were compared. 16th hour cTn-I was insignificantly lower in the preconditioning arm (0.026 µg/l vs. 0.045 µg/l, p = 0.186). The incidence of cTn-I elevation 5-fold above the upper reference limit (URL) (> 0.115 µg/l) was lower in the preconditioning group, but it was also not significant (21.6% vs. 11.8%, p = 0.184). Conclusions : A single episode of RIPC before elective PCI demonstrated less troponin elevation but failed to show a significant effect.